The Evaluation of Equity-Focused Community Coalitions: A Review of the Empirical Literature - Jill Chouinard; Tiffany L. S. Tovey; Kristin Kidd (The Evaluation Center at Western Michigan University, 2023)
Conducting evaluation and research with community coalitions involved in health equity initiatives is inherently complex. In this paper we provide a review and synthesis of the empirical literature on the evaluation of equity-focused community coalitions. We explore issues, challenges, and barriers experienced by evaluators, as well as techniques and approaches that were considered beneficial. Our review identified 11 peer reviewed articles, from which we identified seven overlapping themes: (1) framing equity in the evaluation process, (2) use of multiple theoretical frameworks, (3) use of systems-focused approaches, (4) strategic use of intersectoral partnerships and collaborations, (5) intentional communication and building trusting relationships, (6) challenges dedicating purposeful time to the work, and (7) issues of cultural and contextual clarity and responsiveness. Our findings point to a significant focus on context, history, learning, communication, relationships, and power. The cultural complexity and historical scope of each context, diversity of stakeholders, and enormity of the systemic issues involved, shape and challenge the evaluation and research process in fundamental ways, requiring a creative and kinetic thinking -- a shifting from methodological certainty to an acknowledged uncertainty, where mixing, blending and the innovative use of approaches and theories becomes a way of moving beyond the colonizing past.